Entropy generation over nonlinear thermally radiative and mixed convective nanofluid flow - Ghosh Sharmistha; Chatterjee Sewli; Mondal Hiranmoy (EPJ Web of Conferences)
This study focuses on incompressible nanofluid flow over nonlinear stretching boundary layer with viscous dissipation and thermal radiation. The effect of thermophoresis with diffusive Brownian motion and uniform heat generation or absorption is also studied. The entropy generation analysis is performed for this model. The spectral quasi-linearisation technique is employed to determine the impact of different parameters of interest, as Nusselt and Sherwood numbers. The performance of the numerical scheme is examined through residual error analysis that reveals the robustness of the present method in rendering rapidly convergent solutions.